A plant mechanism of hijacking pathogen virulence factors to trigger innate immunity - Xiao, Yu; Sun, Guangzheng; Yu, Qiangsheng; Gao, Teng; Zhu, Qinsheng; Wang, Rui; Huang, Shijia; Han, Zhifu; Cervone, Felice; Yin, Heng; Qi, Tiancong; Wang, Yuanchao; et al. (Science (American Association for the Advancement of Science), 2024)
Polygalacturonase-inhibiting proteins (PGIPs) interact with pathogen-derived polygalacturonases to inhibit their virulence-associated plant cell wall–degrading activity but stimulate immunity-inducing oligogalacturonide production. Here we show that interaction between Phaseolus vulgaris PGIP2 (PvPGIP2) and Fusarium phyllophilum polygalacturonase (FpPG) enhances substrate binding, resulting in inhibition of the enzyme activity of FpPG. This interaction promotes FpPG-catalyzed production of long-chain immunoactive oligogalacturonides, while diminishing immunosuppressive short oligogalacturonides. PvPGIP2 binding creates a substrate binding site on PvPGIP2-FpPG, forming a new polygalacturonase with boosted substrate binding activity and altered substrate preference. Structure-based engineering converts a putative PGIP that initially lacks FpPG-binding activity into an effective FpPG-interacting protein. These findings unveil a mechanism for plants to transform pathogen virulence activity into a defense trigger and provide proof of principle for engineering PGIPs with broader specificity. Many plant pathogens release cell wall–degrading enzymes to facilitate access into the cell. When cell walls degrade, long-chain wall fragments suppress immune responses, and short-chain fragments can enhance plant immunity. Using biochemical assays and protein structural analysis, Xiao et al . established how a plant polygalacturonase-inhibiting protein (PGIP) interacts with a fungal polygalacturonase enzyme (see the Perspective by Thynne and Kobe). They found that this interaction alters how the fungus binds to cell wall polysaccharides and influences substrate preferences and the types of degradation products generated to increase immunity. Proteins from two different species combine to make an enzymatic complex with different behavior from either alone. Additionally, the authors demonstrate the potential for engineering by modifying a related but inactive PGIP to become active. —Madeleine Seale A plant immunity protein interacts with a fungal cell wall–degrading enzyme to create immunogenic compounds.